2016
DOI: 10.1016/j.jes.2015.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous stability and mobility of C60 complexed by sodium dodecyl benzene sulfonate surfactant

Abstract: Surfactant complexation may have significant effects on the environmental behavior of nano-particles. In order to understand the ecological exposure of nano-materials, it is important to determine the stability and mobility of surfactant-complexed nano-materials in aqueous systems. In this study, the aggregation and transport of C 60 complexed by the surfactant sodium dodecyl benzene sulfonate (SDBS) were investigated. It was found that SDBS-complexed C 60 had a ζ-potential of −49.5 mV under near-neutral pH co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…S4 that the fullerol dispersion has a considerably high stability since its concentra- tion almost did not change for 30 days. This result proves that the fullerol dispersion has a higher mobility than SWNTs modified by SDS of a low concentration [26], oxidized MWNTs [27], and nC 60 colloids [10].…”
Section: Stability and Mobility Of Fullerol Nanoparticlessupporting
confidence: 52%
See 2 more Smart Citations
“…S4 that the fullerol dispersion has a considerably high stability since its concentra- tion almost did not change for 30 days. This result proves that the fullerol dispersion has a higher mobility than SWNTs modified by SDS of a low concentration [26], oxidized MWNTs [27], and nC 60 colloids [10].…”
Section: Stability and Mobility Of Fullerol Nanoparticlessupporting
confidence: 52%
“…Under the near-neutral pH condition, the zeta potential is approximate −30 to −31 mV. In the aqueous environment, zeta potential of nC 60 dispersion is from −15.1 to −29.9 mV in the pH range of 4.3-9.1 [10]. Generally, a higher absolute value of zeta potential of a dispersion presents a higher stability in the aqueous environment.…”
Section: Stability and Mobility Of Fullerol Nanoparticlesmentioning
confidence: 98%
See 1 more Smart Citation
“…50 Finally, the steric effect induced by the deposited surfactant molecules also contributed to saponin's enhancement of GO transport. 66,75,78…”
Section: Resultsmentioning
confidence: 99%
“…50 Finally, the steric effect induced by the deposited surfactant molecules also contributed to saponin's enhancement of GO transport. 66,75,78 Moreover, theoretical calculations that depend on XDLVO theory demonstrated that the particle-collector interaction energy proles were closely linked to the addition of saponin (Fig. S10 †).…”
Section: Papermentioning
confidence: 96%